Macrophage-derived nitric oxide initiates T-cell diapedesis and tumor rejection - Sektioglu, Ibrahim Murathan; Umansky, Viktor; Knebel Doeberitz, Magnus von (OncoImmunology, 2016)
In tumor biology, nitric oxide (NO) is generally regarded as an immunosuppressive molecule that impedes T-cell functions and activation of endothelial cells. Contrasting with this view, we here describe a critical role for NO derived from inducible nitric oxide (iNOS)-expressing tumor macrophages in T-cell infiltration and tumor rejection as shown by iNOS gene deletion, inhibition of iNOS, or NO donors. Specifically, macrophage-derived NO was found to induce on tumor vessels adhesion molecules that were required for T-cell extravasation. Experiments with human endothelial cells revealed a bimodal dose-dependent effect of NO. High doses of NO donors were indeed suppressive but lower, more physiological concentrations, induced adhesion molecules in an NFkB-dependent pathway and preferentially activated transcription of genes involved in lymphocyte diapedesis. iNOS+ macrophages in tumors appear to generate precisely the amount of NO that promotes endothelial activation and T-cell infiltration. These results will be valuable for the development of strategies designed to overcome the paucity of T-cell infiltration into tumors that is a major obstacle in clinical cancer immunotherapy.
Gesehen am 19.02.2019